Social cognitive abilities in older adults with mild cognitive impairment and dementia: Neuropsychiatry and behavioral neurology: Neuropsychiatric symptoms in MCI and dementia. (7th December 2020) - Chander, Russell J.; Numbers, Katya T.; Grainger, Sarah A.; Cleary, Rhiagh; Das, Debjani; Mather, Karen A.; Kochan, Nicole A.; Brodaty, Henry; Henry, Julie D.; Sachdev, Perminder S.
Abstract: Background: Aging is associated with changes in general cognition and social cognition. Many studies have detailed these functions in isolation, comparing young and older adults. More information is needed on how social cognition, including theory of mind (ToM), affective empathy (AE), social perception (SP), and social behavior (SB), is affected at different cognitive stages in older adults. Method: Cross‐sectional study of 305 older adults from the Sydney Memory and Ageing Study. Dementia was classified based on clinical consensus using DSM‐IV criteria, while mild cognitive impairment (MCI) was classified using the International Working Group criteria. Cognitively normal (CN), MCI, and dementia participants were compared on social cognitive domains including: ToM, via the Reading the Mind in the Eyes Test (RMET) and the Interpersonal Reactivity Index – Perspective Taking subscale (IRI‐PT); AE, via the IRI – Empathic Concern subscale (IRI‐EC); and SP, via the Emotion Recognition Task (ERT). Apathy, which is related to SB, was measured via the Apathy Evaluation Scale (AES). Result: Mean age 87.00 ± 4.05 years, mean education 11.89 ± 3.36 years, 60.3% female. 141 were CN, 103 had MCI, and 61 had dementia. Across cognitive groups, significant differences were observed for the RMET, ERT (specifically for the recognition of anger, disgust, and happiness), AES, IRI‐PT, and IRI‐EC. In posthoc comparisons, RMET and ERT were significantly poorer in MCI and dementia compared to CN, but not between MCI and dementia. IRI ratings and AES were poorer for dementia compared to MCI and CN, but not between MCI and CN (Table 1). In multivariable logistic regression adjusting for significant risk factors for cognitive impairment, RMET and ERT disgust performance were associated with lower risk of MCI over CN. Only AES significantly differentiated dementia from MCI (Table 2). Conclusion: Neurocognitive disorders are associated with social cognition changes. ToM and SP appear to be affected in MCI relative to CN. Apathy, known to be linked to SB, appears to be affected in dementia. MCI seems to be associated with impaired ability to recognize specific social cognitive cues, while dementia may be more associated with overall worse social cognitive functioning and observed behavioral changes.